Analisis Perkembangan Return On Assets (ROA) dan Return On Equity (ROE) untuk Mengukur Kinerja Keuangan - Wijaya, Rendi (Universitas muhammadiyah palembang, 2019)
This study aims to determine how the development of Return On Assets (ROA) and Return On Equity (ROE) to assess financial performance at PT. Surya Eka Lestari Ogan Komering Ulu. The results of this study indicate that financial performance at PT. Surya Eka Lestari is good enough because it has reached the ratio standard. The good or bad management of a company can be reflected in the financial performance of a company. Development of Return On Assets (ROA) at PT. Surya Eka Lestari Ogan Komering Ulu from 2013 to 2017 produced an average of 30.87% and had met the standards set above the 1.5% ratio, the ratio achieved was categorized in a healthy group. The higher the return on assets produced, the higher the net profit generated from each fund that is embedded in the total assets. While the development of Return On Equity (ROE) at PT. Surya Eka Lestari Ogan Komering Ulu from 2013 to 2017 produced an average of 43.50% and had met the industry average of 40%, the ratio achieved showed the company's condition was quite good. The higher the yield, the better because the dividends distributed or reinvested as retained earnings are also greater.